The Sinicization of Christianity in Mainland Church - Zhou, Zhaozhen (Transformation, 2026)
Sinicization of religion is a national policy of China. It includes the Sinicization of Christianity. In sum, Sinicization of religion is, politically, to recognize the leadership of the Communist Party of China; culturally, to integrate the fine traditions and Chinese culture and, socially, to adapt to Chinese society and do things that are beneficial to society and the nation. Its significance to the church is enormous, and there are risks and opportunities. Since Christian missionaries came to spread Christianity in China, counting from the time of the Nestorians, Sinicization is always an ongoing process. Regarding the present movement of Sinicization, there are however different responses and skeptical comments, both from inside and outside the church. Some are of genuine concerns, but there are also of fears, misunderstandings and ignorance. Today the church has been occupied with shepherding the herds, and as a result, lacking in theological building.